Insights Into the Mechanisms of Phreatic Eruptions From Continuous High Frequency Volcanic Gas Monitoring: Rincón de la Vieja Volcano, Costa Rica - Battaglia, Angelo; de Moor, J. Maarten; Aiuppa, Alessandro; Avard, Geoffroy; Bakkar, Henriette; Bitetto, Marcello; Mora Fernández, M. M.; Kelly, Peter; Giudice, Gaetano; Delle Donne, Dario; Villalobos, Hairo (Frontiers in Earth Science, 2019)
Rincón de la Vieja (10.49 N, 85.19 W), the northernmost active volcano in Costa Rica, hosts a hot acidic crater lake, which frequently produces large phreatic to phreatomagmatic eruptions. Relatively little is known about this volcano, as it is poorly monitored due to remote location and difficulty of access. In February-May 2017, we deployed a Multi-GAS instrument to continuously monitor gas concentrations in the plume released by the vigorously degassing crater lake. The Multi-GAS station registered gas information from February 3 to May 9, 2017, a period during which many phreatic to phreatomagmatic eruptions occurred, 42 of which were recorded seismically. Nine of these eruptions were also registered in the Multi-GAS record as distinct gas pulses, representing the first measurements of gases explosively released during individual phreatic/phreatomagmatic explosions. Our results show that during background quiescent degassing the Rincón de la Vieja crater lake plume was characterized by high CO2/SO2 ratios (64±59) and H2S/SO2 ratios of 0.57±0.20. This composition is interpreted as reflecting hydrothermal (re)processing of magma-sourced gas in the sub-limnic environment. Phreatic blasts were recorded by the Multi-GAS as brief (1-2 minutes long) pulses of elevated gas mixing ratios (up to ~ 52 ppmv SO2 and > 3000 ppmv CO2), or more than an order of magnitude higher than during background degassing (~ 1 ppmv SO2 and ~ 450 ppmv CO2). During the phreatic eruption(s), the H2S/SO2 ratio was systematically lower (<0.18) than during background degassing, but the CO2/SO2 ratio remained high (and variable), ranging from 37 to 390. These compositions indicate a S-poor eruptive gas, suggesting that the source magmatic gas is extensively processed during pre-eruptive hydrothermal storage, most likely by native S deposition and by sulfate formation. Our gas results are thus overall consistent with a mechanism of phreatic eruptions triggered by accumulation of magmatic-hydrothermal gases beneath a hydrothermal system. We conclude that real-time Multi-GAS monitoring can provide key insights into the mechanisms driving phreatic eruptions at Rincón de la Vieja, and perhaps at other similar volcanic lakes.